The civil protection of trademarks according to the UAE law - Yas, Nadia; Abdurahim, Hani; Njim, Mohammed (Research Journal in Advanced Humanities, 2024)
The civil protection of trademarks in the United Arab Emirates is governed by Federal Law No. 37 of 1992 on Trademarks. This law outlines the legal framework for registering, protecting, and enforcing trademarks in the UAE. It provides trademark owners with the legal tools to safeguard their intellectual property rights and take appropriate measures in case of any infringement or unauthorised use of their trademarks. The law plays a crucial role in maintaining a fair and competitive business environment while ensuring the country's intellectual property protection.